2017
DOI: 10.1097/md.0000000000007914
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of female pelvic organ prolapse with and without urinary incontinence

Abstract: The study reports a single center experience with surgical management of female pelvic organ prolapse (POP) with and without urinary incontinence.Between January 2006 and July 2016, 93 consecutive patients with anterior and/or apical symptomatic POP underwent abdominal sacrocolpopexy (ASC) or laparoscopic sacrocolpopexy (LSC) or pubovaginal cystocele sling (PCS); 25 patients had concomitant stress urinary incontinence (SUI). Subjective outcome was assessed by the Pelvic Floor Impact Questionnaire (short form) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…[ 6 , 7 ] Some urologists also made many attempts such as using autologous fascia sling as an alternative method to mesh sling to treat SUI with pelvic organ prolapse. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 , 7 ] Some urologists also made many attempts such as using autologous fascia sling as an alternative method to mesh sling to treat SUI with pelvic organ prolapse. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of malignant tumors is characterized by multivessel diffuse distribution inside the septum or solid components, while the number of blood vessels in benign tumors is lower than that of malignant tumor, with the blood vessels of benign tumors being mainly located around the lesion. Benign tumors may also be characterized by a lack of blood flow (14,15). Celiesiute et al (16) and other researchers have found that benign and malignant pelvic tumors have their own characteristics in terms of blood vessel formation and blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of patients had pelvic organ prolapse (POP) associated to SUI. [33] MS could be considered as a conservative and noninvasive treatment for concomitant SUI and de novo SUI. To determine the efficacy of MS for SUI in the presence of POP, a prospective study is needed.…”
Section: Discussionmentioning
confidence: 99%